Acoustic characterization of historic cloisters in Portugal - António P. O. Carvalho (2004)
This paper presents the results of field measurements in 20 cloisters of old monasteries in Portugal (length: 15 to 55 m and height: 3.7 to 8.5 m) regarding their acoustic behavior to some objective parameters: RT, RASTI and background sound level. The individual results show, for instance, that the mean measured values in each cloister for RASTI were from 0.33 to 0.64 (with a global mean value of 0.50 for all rooms) and for the RT (1 kHz) were from 1.0 to 4.5 s (with a global mean of 2.5 s for all rooms). The evaluation of the sound level difference between cloister and exterior (LA95), found values up to 24 dB(A) with a global average of a 7 dB(A) for all rooms. The sound level decrease from one corner to the opposite one (diagonal) was also measured and values from 4 to 15 dB(A) were found (with a global average of 9 dB(A) for all spaces). A small group of rooms with a covered patio or glass-closed galleries was tested to check for differences in their acoustic behavior regarding the typical cloister nature. Simple formulas were obtained that relate among the objective acoustic parameters and between the acoustic and architectural parameters.